AKADEMI SEPAKBOLA DENGAN METODE SUPERIMPOSISI DI BANJARBARU - Rizky, Muhammad; Agusniansyah, Nursyarif (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Indonesia South Kalimantan has the potential of a quality football player. With the potential of a good football player, this potential must be developed and directed to be even better. Banjarbaru became a development city after Banjarbaru became the capital of South Kalimantan. The design of the Football Academy using the superimposition method in Banjarbaru aims to have a positive influence on users in creating professional soccer players. This method aims to influence each user's activity for the better. To support the superimposition method, the use of modern architectural concepts is used which aims to influence human behavior driven by design.